Gene targeting using the Agrobacterium tumefaciens-mediated CRISPR-Cas system in rice - Xu, Rongfang (Springer, 2014)
BACKGROUND: The type II clustered, regularly interspaced, short palindromic repeat (CRISPR)/ CRISPR-associated protein 9 (Cas9) system is a novel molecular tool for site-specific genome modification. The CRISPR-Cas9 system was recently introduced into plants by transient or stable transformation. FINDINGS: Here, we report gene targeting in rice via the Agrobacterium tumefaciens-mediated CRISPR-Cas9 system. Three 20-nt CRISPR RNAs were designed to pair with diverse sites followed by the protospacer adjacent motif (PAM) of the rice herbicide resistance gene BEL. After integrating the single-guide RNA (sgRNA) and Cas9 cassette in a single binary vector, transgenic rice plants harboring sgRNA:Cas9 were generated by A. tumefaciens-mediated stable transformation. By analyzing the targeting site on the genome of corresponding transgenic plants, the mutations were determined. The mutagenesis efficiency was varied from ~2% to ~16%. Furthermore, phenotypic analysis revealed that the biallelic mutated transgenic plant was sensitive to bentazon. CONCLUSIONS: Our results indicate that the agricultural trait could be purposely modified by sgRNA:Cas9-induced gene targeting. CRISPR-Cas9 system could be exploited as a powerful tool for trait improvements in crop breeding.